Visual assessment of leaf area index in coffee (Coffea arabica L.) fields - Sergio A. Castro-Pacheco; María I. González-Lutz; José M. Araya-Alfaro; Mariano Vargas-Chinchilla; Marco V. Gutiérrez-Soto (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The application of leaf area index (LAI) in coffee crop management depends on the availability of methodologies for proper estimation. The objective of this study was to develop a methodology for the visual assessment of LAI in coffee fields and to establish a protocol for training, evaluation, and feedback for evaluators. Four rounds of LAI measurements were conducted using visual estimates, two instruments (LAI 2200-C and AccuPAR LP-80), and defoliation of coffee hedgerows in Poás, Costa Rica. In each round, five workers visually estimated the LAI values on two occasions separated by 15 days, and feedback reinforcement was provided to each worker at the end of each round. Visual assessments showed high repeatability and reproducibility and the estimates were adjusted to the linear regression model in most cases. Evaluators improved their capacity to visually assess the LAI throughout the rounds, as the value of R2increased consistently for most workers, with values as high as 0.87. Instrumentation evaluation of LAI produced R2values of 0.5-0.6, with significant underestimation bias. The performance of the different methods is discussed in the context of widely spaced hedgerows. The proposed visual methodology constitutes a statistically sound, rapid, simple, and reliable method for determining the LAI of coffee fields to aid in decision-making for crop management.